2022
DOI: 10.3390/cancers14020432
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Surgical Extent in Patients with Unilateral Multifocal Papillary Thyroid Carcinoma

Abstract: Multifocality increases the risk of recurrence in patients with papillary thyroid carcinoma (PTC); however, it is unclear whether multifocality justifies more extensive or aggressive surgical treatment. Here, we evaluated the effect of the operative extent on the recurrence-free survival (RFS) of patients with multifocal PTC. Between 2010 and 2019, 718 patients with unilateral multifocal PTC were enrolled; 115 patients (16.0%) underwent ipsilateral thyroid lobectomy, and 606 patients (84.0%) underwent total th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 29 publications
0
2
0
1
Order By: Relevance
“…Current knowledge suggests that cervical lymph node metastasis is the most crucial variable to increase the risk of local recurrence and overall survival ( 6 ). Our recent study ( 7 ) and studies by others ( 8 , 9 ) have suggested that MPTC increases the risk of cervical lymph node metastasis. Cervical lymph node metastasis is often accompanied with a poor prognosis, including distant metastasis and persistent or recurrent disease.…”
Section: Introductionmentioning
confidence: 65%
“…Current knowledge suggests that cervical lymph node metastasis is the most crucial variable to increase the risk of local recurrence and overall survival ( 6 ). Our recent study ( 7 ) and studies by others ( 8 , 9 ) have suggested that MPTC increases the risk of cervical lymph node metastasis. Cervical lymph node metastasis is often accompanied with a poor prognosis, including distant metastasis and persistent or recurrent disease.…”
Section: Introductionmentioning
confidence: 65%
“…Крім того, установлено, що двобічні та однобічні МФ карциноми мали однакову частоту локорегіонарних і віддалених рецидивів, білатеральність при багатовогнищевому ПРЩЗ не пов'язана з гіршим прогнозом, а більшість випадкових контралатеральних пухлин є мікрокарциномами і не змінюють категорії ризику рецидиву та виживання [98]. Наявність однобічної МФ у пацієнтів після ЛЕ не мала суттєвого впливу на регіонарний рецидив [33,40,128] чи вірогідність контралатерального ПРЩЗ та виживаність хворих [45]. Відсутність самостійного прогностичного впливу МФ на клінічні результати продемонстували результати кількох досліджень [42,53,110].…”
Section: Lectures • лекціїunclassified
“…They proposed that multifocal PTMC should be treated using strategies different from those of multifocal macro-PTC (11). Harries et al (12) and Woo et al (13) further suggested that multifocal PTC should not be considered an indication for completion thyroidectomy. Geron et al revealed that multifocality is not an independent prognostic factor, as proven by propensity score-matching analysis (14).…”
mentioning
confidence: 99%